2012
DOI: 10.1177/1933719111426605
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthin, a Chinese Medicine for the Medical Treatment of Ectopic Pregnancy With High Levels of β-hCG

Abstract: This was a retrospective study of the effectiveness of trichosanthin (TCS), an active component isolated from the Chinese herb root tuber of Trichosanthes kirilowii on 140 cases of ectopic pregnancy with higher levels of β-human chorionic gonadotropin (β-hCG) managed with a single dose of TCS treatment. Trichosanthin has been used for medical treatment of ectopic pregnancy in China since the 1980s. This study was performed in a major teaching hospitals in China. The mean pretreatment level of β-hCG in the TCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Recently, a large clinical study indicated that TCS was effective against ectopic pregnancy in 140 women (28.9 years, range 18 to 44) at the dose of 1.8 mg/person using intramuscular injection. There were no significant side effects for most of the patients and it seems to have no effects on their subsequent pregnancy as well as giving birth to a healthy baby [51]. However, the efficiency as well as recommended dosage of TCS on breast cancer patients will depend on further clinical trials.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a large clinical study indicated that TCS was effective against ectopic pregnancy in 140 women (28.9 years, range 18 to 44) at the dose of 1.8 mg/person using intramuscular injection. There were no significant side effects for most of the patients and it seems to have no effects on their subsequent pregnancy as well as giving birth to a healthy baby [51]. However, the efficiency as well as recommended dosage of TCS on breast cancer patients will depend on further clinical trials.…”
Section: Discussionmentioning
confidence: 97%
“…The dried products of male T . kirilowii roots, a kind of famous traditional Chinese medicine known as “radix trichosanthis”, have been extensively used in the treatment of ectopic pregnancy 1 and bloat-resistant lesions 2 . Trichosanthin (TCS), the active ingredient of radix trichosanthis, is a type I single chain ribosome-inactivating protein (SCRIP) 3 4 that plays a specific role in inhibiting protein synthesis 5 6 .…”
mentioning
confidence: 99%
“…TCS has widely been used to cure diabetes, rigorous coughing, breast abscesses 7 , hypertension, hyperlipidemia, blood plasmic viscosity 8 , migraines 9 , exfetation, vesicular moles, and ectopic gestation 1 10 . TCS has effects on treatments for different tumours and cancers such as malignant tumours 11 12 , epithelial cancer 13 , prostatic cancer 14 , and cervical cancer 15 .…”
mentioning
confidence: 99%
“…Trichosanthin (TCS), from the root of Trichosanthes kirilowii Maxim. , is a type I ribosome-inactivating protein and has been clinically used for hydatidiform mole, extrauterine pregnancy, stillbirth, and abortion in China for decades 13 . Notably, TCS can effectively inhibit tumors like fibrosarcoma 14 and glioma 15 , and restore the sensitivity of tumors to chemotherapeutics 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%